Effect of the TLR9 signaling pathway on acyclovir infection with herpes simplex virus type 2 in HaCaT cells - Shi, Jialing; Kuang, Lin; Qi, Li; Li, Ruoyu; Wu, Yangfan (Frontiers in Microbiology, 2025)
IntroductionThe objective of this study was to investigate the effect of acyclovir (ACV) on the TLR9 signaling pathway after human immortalized epidermal (HaCaT) cell infection with herpes simplex virus type 2 (HSV-2).MethodsIn this study, an in vitro cell model of HSV-2 infection was successfully constructed by infecting HaCaT with HSV-2 virus. In order to explore the antiviral mechanism of acyclovir (ACV), high-throughput transcriptome sequencing (RNA-seq) was used to analyze the genome-wide expression profiling of infected cells before and after ACV treatment, and to systematically compare the change characteristics of differentially expressed genes (DEGs). Based on the sequencing results, the study further focused on Toll-like receptor (TLR) 9 signaling, using quantitative real-time reverse transcriptase chain reaction (qRT-PCR) to quantitatively detect the effect of ACV intervention on the mRNA expression level of key molecules of TLR 9 signaling pathway in HSV-2 infected HaCaT cells.ResultsA total of 896 significant changes in gene expression were identified by the transcriptome analysis, including 314 upregulated genes and 582 downregulated genes. GO enrichment analysis showed that the differentially expressed genes were mainly related to CC includes the ubiquitin ligase complex, mitochondrial protein-containing complex, DNA-binding transcription activator activity, exonuclease activity, catabolic process, nuclear-transcribed mRNA catabolic process nuclear-transcribed mRNA catabolic process; KEGG enrichment analysis showed that the differentially expressed genes were mainly related to Toll-like receptor signaling pathway, herpes simplex virus 1 infection, and TNF signaling pathway. The RT-PCR results were confirmed to be basically consistent with the sequencing results.ConclusionACV altered the transcriptome level of HSV-2 infection in HaCaT cells. The RT-PCR results confirmed that ACV intervened in HSV-2 infection through the TLR9 signaling pathway.